PERAN SEKOLAH DALAM PEMBINAAN NILAI-NILAI AGAMA DAN SOSIAL PADA SISWA SDK WOLOMELI - Ngongo, Thomas Seingo (Jurnal Analisis Pendidikan Sosial, 2024)
This study aims to explore the role of SDK Wolomeli in fostering religious and social values among its students. Using qualitative methods, including interviews, observations, and documentation, data were collected from the principal, teachers, and students. The findings indicate that SDK Wolomeli actively implements various programs and activities to instill religious and social values among students. Firstly, the school demonstrates a strong commitment to religious value education through activities such as collective prayers and support for religious events. These programs contribute to the development of tolerance among students. However, challenges include limited time in the curriculum and the need for additional teacher training to enhance the effectiveness of religious value instruction. Secondly, the school has successfully integrated social values through extracurricular activities and community programs, such as public facility clean-ups and aid to underprivileged residents. These activities support the development of empathy and solidarity among students. Nevertheless, there are obstacles related to inconsistent student participation and resource limitations. Thirdly, parental and community involvement in supporting the education of religious and social values needs improvement. Although there are forms of engagement, such as parent events and community programs, enhancing communication and collaboration with families could strengthen the instillation of these values. Overall, SDK Wolomeli has shown significant efforts in instilling religious and social values, but there is room for improvement in implementation and resource support. This study provides valuable insights for designing more effective strategies to support character development in students in the future.